Convention between Great Britain and the United States [electronic resource] : for the submission to arbitration of British claims in connection with the Behring Sea seal fishery - Great Britain.; United States 1896 Feb. 8. Treaties, etc. Great Britain,3 (London : Printed for H.M.S.O. by Harrisson and Sons, 1896)
Original issued in series: [Command papers / Great Britain. Parliament] Cd. 8101. At head of title : Treaty series. No. 10. 1896. "Presented to both Houses of Parliament by Command of Her Majesty. June 1896." Electronic reproduction. Mode of access: Internet. 44